2018
DOI: 10.1186/s12872-018-0868-3
|View full text |Cite
|
Sign up to set email alerts
|

Admission homocysteine is an independent predictor of spontaneous reperfusion and early infarct-related artery patency before primary percutaneous coronary intervention in ST-segment elevation myocardial infarction

Abstract: BackgroundSpontaneous reperfusion (SR) and early infarct related artery (IRA) patency before primary percutaneous coronary intervention (PPCI) might bring extra benefit for patients with ST-segment elevation myocardial infarction (STEMI). This study premilinarily screened the independent predictors of SR, and assessed the relationship between SR and plasma homocysteine (HCY).MethodsThe medical records of 998 patients who were diagnosed as STEMI and underwent emergency coronary angiography were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…Despite the fact that certain determinants of the patency of the IRA are well-known (younger age, the absence of significant concomitant diseases, a lower contents of lipoprotein (a), total cholesterol, homocysteine, etc. ), the exact mechanism of blood flow preservation through the IRA remains unclear (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that certain determinants of the patency of the IRA are well-known (younger age, the absence of significant concomitant diseases, a lower contents of lipoprotein (a), total cholesterol, homocysteine, etc. ), the exact mechanism of blood flow preservation through the IRA remains unclear (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HHcy was a potential predictor for SCF prognosis and related to cumulative cardiac events. 14 Moreover, Li et al 17 observed that increased plasma tHcy levels (≥17.55 μmol/L) were independent negative predictor of spontaneous reperfusion (defined as achievement of TIMI grade III flow in the infarct-related artery (IRA) before primary PCI) in patients with AMI, implying the potential relationship between HHcy with less early IRA patency. However, to our knowledge, there is no detailed study evaluating the relationship between plasma tHcy levels and SCF measured by mean CTFC in patients with AMI.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in this study that symptom onset to hospital arrival time has an effect on the pre-pPCI TIMI flow rate; those patients who came to the hospital earlier have a higher rate of TIMI III flow rate as compared to later comers. The relationship between the late arrival to hospital and TIMI III flow was proven by other studies; it was found that if total ischemic time is higher then there is less chance of TIMI III flow rate in STEMI patients [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 92%